Khulāṣat al-ashʿār wa-zubdat al-afkār. Volume 6.2 : Bakhsh-i Iṣfahān - Kāshānī, Mīr Taqī al-Dīn, (Miras Maktoob, ISBN: 9789004365452., 2019)
In Persian literature, tadhkira ('note', 'memorandum') works are for the most part collections of biographies of poets, combined with selections from their writings. The earliest such work is Dawlatshāh Samarqandī's Tadhkirat al-shuʿarāʾ (completed in 892/1487), which set a standard for posterity. The tadhkira genre was especially popular in the 10th/16th century and following. The work by Mīr Taqī al-Dīn Kāshānī (alive in 1016/1607) published here is an important example of this. It consists of an introduction, four divisions, and an epilogue ( khātima ), six volumes in all. From among these volumes, the epilogue listing some 394 poets from specific cities and regions in the Persianate world, many of whom were contemporaries of the author, is of special interest. Having met with many of them on his literary travels, their biographies contain a lot of information on the social and cultural climate of the time, besides new poets and poems. This volume: 6.2, Isfahan.